Supporting the professional women's transition to motherhood through maternity coaching: a South African perspective - Yasar, Aneshrie (My University, 2017)
“The obligation for working-mothers is a very precise one: the feeling that one ought to work as if one did not have children, while raising one’s children as if one did not have a job.” – Annabel Crabb, Author of The Wife Drought Women play a vital role in organisations, yet world-wide remain under-represented in key leadership positions. South Africa is no different. In addition, research indicates that professional women are ‘opting-out’ of the talent pipeline, further reducing the pool of women available to step in to senior leadership roles. Becoming a mother is life-changing, and when combined with a desire for a fulfilling career, role-conflict can occur. The guilt which accompanies role-conflict can often be overwhelming and may lead to professional women exiting organisations, taking with them valuable industry knowledge and expertise. Hence, retaining female talent is increasingly becoming a business imperative. This study aims to contribute to the field of Business Coaching by researching Maternity ‘Transition’ Coaching in an organisational context. As such, the study explored four research questions aimed at providing a systemic view of the experiences of professional women during the maternity transition period, the line manager’s role during this period, the influence of organisational culture on working-mothers, and the emergence of maternity transition coaching as a support mechanism in organisations. Following a detailed review of the literature, the research methodology of a qualitative, multiple-case study approach was selected. Two organisations (cases) were researched using semi-structured face-to-face interviews with 15 respondents, as the primary sources of data collection. The research was further supported by an analysis of secondary data, both of which allowed for a full investigation of the research questions. The key findings indicated that maternity transition coaching is a strategic necessity for organisations wishing to attract and retain female talent in the 21st Century. Transitional theory along with an understanding of life and career stages are important aspects of this genre of coaching. Coaching increased support at critical transition points, leading to the retention of the professional women in the study along with a more seamless re-integration with their careers. Further, it surfaced that line managers play a critical role in a successful maternity transition, and as such also require support. It was further concluded that a family-friendly organisational culture is an enabler to a successful maternity transition. Maternity transition coaching therefore supports professional women in their desire for a satisfying career and work-life integration.
A research report submitted to the Faculty of Commerce, Law and Management, University of the Witwatersrand, in partial fulfilment of the requirements for the degree of Master of Management in Business Executive Coaching Johannesburg, 2017
Keywords: Work and family--South Africa; Women--Employment--South Africa; Women executives--South Africa; Executive coaching--South Africa